AUDIÊNCIA DE CUSTÓDIA: a importância da abordagem multidisciplinar no acesso à justiça - THAIS DALMOLIN CERVO (2024)
In this paper, a study is conducted on access to justice and the respect for human dignity in the face of a culture of incarceration, analyzed through critical criminology, developing a narrative that highlights the interdisciplinary nature within the Judiciary by including the psychosocial support team for detained individuals in the custody hearing procedure. The question under debate is how the Judiciary, in its judicial role, can provide protection for fundamental rights and, thus, mitigate the culture of incarceration through the foundation provided by psychosocial support and the possibilities of referral to the established network of public psychosocial and health services. The study begins with the conceptualization of access to justice and human dignity, as well as the perspective of the culture of incarceration. Next, the pre-trial hearings are presented from their beginnings, covering terminology, concept, admissibility, and purposes. Finally, the role of the Judiciary as an agent of public policies at the gateway to the prison system is analyzed, discussing the joint action between the ONU and CNJ for the implementation of pre-trial hearings in a multidisciplinary manner, providing psychosocial care and referral for detainees, with the presentation of data in Campo Grande/MS in the first semester of 2023, aiming to guarantee the rights of people in custody. This involves considering the life context and psychosocial aspects, facilitating access to service networks that promote care, citizenship, and social inclusion. The legal debate remains current, especially after 2015, when a decision by the Federal Supreme Court determined the installation of pre-trial hearings nationwide, and the installation process is still ongoing. The research is descriptive/empirical analytical, through bibliographical and documentary research, and also hermeneutical/interpretative regarding the application of national and international legal norms.